2011
DOI: 10.1007/s00404-011-1983-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Laparoscopic ovarian diathermy after clomiphene failure in polycystic ovary syndrome: is it worthwhile? A randomized controlled trial

Abstract: LOD during the 6 months follow-up period and CC for up to six further cycles are equally effective for achieving pregnancy in CC failure PCOS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Nevertheless, the strongest effect size was for the studies by Abu Hashim et al, which were large trials with good quality scores. The QE model RR for all 14 data sets that reported this outcome was 1.43 (95% CI 1.22-1.66) suggesting that the lean -Ojaimi (2003) 21.6 ± 2.5 32.9 ± 5.0 Amer et al (2002) 22.2 ± 1.4 30.3 ± 3.5 Amer et al (2004) 22.2 ± 1.5 30.1 ± 3.7 Poujade et al (2011) 22.7 ± 3.4 28.8 ± 3.0 Zhu et al (2010) 22.4 ± 2.1 26.7 ± 2.8 Nasr (2010) 22.1 ± 1.3 30.4 ± 2.1 Abu Hashim et al (2010) 21.7 ± 1.5 32.6 ± 2.1 Abu Hashim et al (2011a) 22.1 ± 1.2 32.4 ± 2.2 Abu Hashim et al (2011b) 21.8 ± 1.6 32.3 ± 2.3 Abu Hashim et al (2011c) 21.4 ± 2.1 28.2 ± 2.7 Ramzy et al (2001) 23.3 ± 1.1 28.6 ± 2.2 Zakherah et al (2010) 23.1 ± 1.5 31.1 ± 1.9 PCOS women had 43% increase in ovulation rate after OAT compared with obese PCOS women (Figure 2). The RE model RR is depicted for comparison in Supplementary Figure S1.…”
Section: Primary Outcome: Ovulation Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the strongest effect size was for the studies by Abu Hashim et al, which were large trials with good quality scores. The QE model RR for all 14 data sets that reported this outcome was 1.43 (95% CI 1.22-1.66) suggesting that the lean -Ojaimi (2003) 21.6 ± 2.5 32.9 ± 5.0 Amer et al (2002) 22.2 ± 1.4 30.3 ± 3.5 Amer et al (2004) 22.2 ± 1.5 30.1 ± 3.7 Poujade et al (2011) 22.7 ± 3.4 28.8 ± 3.0 Zhu et al (2010) 22.4 ± 2.1 26.7 ± 2.8 Nasr (2010) 22.1 ± 1.3 30.4 ± 2.1 Abu Hashim et al (2010) 21.7 ± 1.5 32.6 ± 2.1 Abu Hashim et al (2011a) 22.1 ± 1.2 32.4 ± 2.2 Abu Hashim et al (2011b) 21.8 ± 1.6 32.3 ± 2.3 Abu Hashim et al (2011c) 21.4 ± 2.1 28.2 ± 2.7 Ramzy et al (2001) 23.3 ± 1.1 28.6 ± 2.2 Zakherah et al (2010) 23.1 ± 1.5 31.1 ± 1.9 PCOS women had 43% increase in ovulation rate after OAT compared with obese PCOS women (Figure 2). The RE model RR is depicted for comparison in Supplementary Figure S1.…”
Section: Primary Outcome: Ovulation Ratesmentioning
confidence: 99%
“…The final 15 studies meeting the inclusion criteria and included in this meta-analysis are summarized in Table 1. In two studies, only ovulation per women data (Abu Hashim et al, 2011a) or pregnancy per women data (Abu Hashim et al, 2011c) was available. Seven studies were randomized controlled trials (RCT) (Abu Hashim et al, 2010Hashim et al, , 2011bNasr, 2010;Palomba et al, 2010;Zakherah et al, 2010;Zhu et al, 2010), the rest being cohort studies.…”
Section: Characteristics Of Studies and Subjectsmentioning
confidence: 99%
“…The authors concluded that LOD is not superior to CC as a Wrst-line treatment of ovulation induction in women with PCOS [69]. Moreover, in a recent RCT, we compared the eYcacy of LOD versus continuation of CC for up to six further cycles in 176 infertile PCOS patients who failed to achieve pregnancy despite previous successful CC induced ovulation [70]. The clinical pregnancy rate per patient and the cumulative pregnancy rate after six cycles were comparable in both groups (39 vs. 33.7% and 47 vs. 39.2%, respectively).…”
Section: Laparoscopic Ovarian Diathermy (Lod)mentioning
confidence: 94%
“…Miscarriage and live birth rates were comparable in both groups. Accordingly, we concluded that LOD during the 6 months follow up period and CC for up to six further cycles are equally eVective for achieving pregnancy in CC failure PCOS patients [70].…”
Section: Laparoscopic Ovarian Diathermy (Lod)mentioning
confidence: 98%
“…[ 6 9 10 11 15 ] Royal College of Obstetricians and Gynecologists,[ 16 ] American College of Obstetricians and Gynecologists,[ 17 ] Society of Obstetricians and Gynecologists, Canada[ 8 ] and the recent PCOS consensus working group[ 4 ] — All recommend its use in highly selected cases, particularly in those with hypersecretion of luteinizing hormone (LH), normal body mass index, those needing laparoscopic assessment of the pelvis or who live too far away from the hospital for the intensive monitoring required during gonadotropin therapy. Despite its theoretical advantages, LOD is not superior to CC, neither as a first line therapy for OI[ 11 18 ] nor for CC-failure[ 19 ] or prior to in vitro fertilization (IVF). [ 11 ] A recent Cochrane systematic review of 9 RCTs and 16 trials concluded that there was no evidence of a significant difference in rates of clinical pregnancy (39.7 vs. 40.5%) or live birth (34 vs. 38%) in women with clomiphene-resistant PCOS undergoing LOD compared to other medical treatments.…”
Section: Methodsmentioning
confidence: 99%